Pengaruh Inflasi, Jumlah Uang Beredar, Dan Sertifikat Bank Indonesia Syariah Terhadap Indeks Saham Syariah di Jakarta Islamic Index - Anisa Ainun Nalda; Rusdi (DPPM Universitas Pelita Bangsa, 2023)
This study aims to determine the effect of macro variable inflation, the money supply, dan Islamic Bank Certificates of Indonesia on the Jakarta Islamic Index. The research population consisted of 60 populations using a saturated sample of 60 samples. The methodology used in this study is multiple linear regression analysis using time series data and using SPSS 25 software. Based on the partial test results it was found that Inflation and Islamic Bank Certificates of Indonesia did not have a significant effect, and the money supply had a negative effect on the Jakarta Islamic Index. In simultaneous testing of inflation, the money supply and Islamic bank certificates of Indonesia jointly afeect the Jakarta Islamic Index.